Analysis of variability in Cardamom mosaic virus isolates occurring in India using symptomatology and coat protein gene sequence - C N Biju, A Siljo, A I Bhat, (Journal of Spices and Aromatic Crops, 2013)
Coat protein (CP) gene from six symptomatologically distinct isolates of Cardamom mosaic virus (CdMV) causing mosaic disease of cardamom collected from different geographical areas were amplified, cloned, sequenced, compared among themselves and with other CdMV isolates available in the GenBank. Identity of coat protein sequence among the isolates varied from 74.8%–99.3% and 80.9%–99.2% at nucleotide and amino acid levels, respectively. Based on the identity, isolates were classified into three distinct groups. All isolates from Karnataka (except Sirsi) belonged to one group, while isolates from Kerala and Tamil Nadu belonged to the other group. Multiple sequence alignment and phylogenetic analyses confirmed grouping of isolates based on percent identities.